2017
DOI: 10.3847/1538-4357/836/1/76
|View full text |Cite
|
Sign up to set email alerts
|

Powerful H2 Line Cooling in Stephan’s Quintet. II. Group-wide Gas and Shock Modeling of the Warm H2 and a Comparison with [C ii] 157.7 μm Emission and Kinematics

Abstract: We map for the first time the two-dimensional H 2 excitation of warm intergalactic gas in Stephanʼs Quintet on group-wide (50×35 kpc 2 ) scales to quantify the temperature, mass, and warm H 2 mass fraction as a function of position using Spitzer. Molecular gas temperatures are seen to rise (to T > 700 K) and the slope of the power-law density-temperature relation flattens along the main ridge of the filament, defining the region of maximum heating. We also performed MHD modeling of the excitation properties … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
106
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(112 citation statements)
references
References 69 publications
5
106
0
Order By: Relevance
“…In the Z sfdbk simulation, the fluxes for the pure rotational lines 0-0 S(1), 0-0 S(3) and 0-0 S(5) are much lower (by at least a factor of 10) than the overall flux, and remain two orders of magnitude below the detection limit at z = 7.2, indicating that their detection at such high redshifts will be challenging, requiring some unusual event, such as a starburst in a major merger. For Z Nsfdbk, on the other hand, the flux of the strongest line 0-0 S(1) reaches FH 2 [0-0 S(1)] ∼ 10 −23 W m −2 at z = 7.2, which is possible to detect with a factor of 10 enhancement from (strong) gravitational lensing (Appleton et al 2010) or shocks, as observed in Stephan's Quintet (Appleton et al 2017). Note that the simulated haloes with M ∼ 10 10 M are not the most massive ones at z ∼ 7.…”
Section: Molecular Hydrogen Emissionmentioning
confidence: 96%
“…In the Z sfdbk simulation, the fluxes for the pure rotational lines 0-0 S(1), 0-0 S(3) and 0-0 S(5) are much lower (by at least a factor of 10) than the overall flux, and remain two orders of magnitude below the detection limit at z = 7.2, indicating that their detection at such high redshifts will be challenging, requiring some unusual event, such as a starburst in a major merger. For Z Nsfdbk, on the other hand, the flux of the strongest line 0-0 S(1) reaches FH 2 [0-0 S(1)] ∼ 10 −23 W m −2 at z = 7.2, which is possible to detect with a factor of 10 enhancement from (strong) gravitational lensing (Appleton et al 2010) or shocks, as observed in Stephan's Quintet (Appleton et al 2017). Note that the simulated haloes with M ∼ 10 10 M are not the most massive ones at z ∼ 7.…”
Section: Molecular Hydrogen Emissionmentioning
confidence: 96%
“…More recently Spitzer IRS observations have shown that our census of the warm H 2 gas in galaxies may be severely incomplete, revealing a new class of galaxies (including ellipti-cal galaxies, AGN, galaxy groups, and galaxy clusters) with strongly enhanced H 2 rotational emission lines, while classical star formation indicators (far-infrared continuum emission, ionized gas lines, polycyclic aromatic hydrocarbons, PAHs) are strongly suppressed (Appleton et al, 2006;Ogle et al, 2007;Guillard et al, 2009;Cluver et al, 2010;Ogle et al, 2010;Guillard et al, 2012b;Ogle et al, 2012;Peterson et al, 2012;Guillard et al, 2015a). Among the sample of H 2 -luminous objects, the Stephan's Quintet is certainly the object where the astrophysical context is clear enough to identify the dominant source of energy that powers the H 2 emission and to associate it with the mechanical energy released in a galactic collision (Guillard et al, 2009(Guillard et al, , 2012aAppleton et al, 2013Appleton et al, , 2017. In these sources, the luminosity of the H 2 lines cannot be accounted for by UV or X-ray excitation, and their properties suggest that the dissipation of turbulence is the main heating mechanism for the warm H 2 gas.…”
Section: H 2 Transitions and Specific Diagnostic Powermentioning
confidence: 99%
“…This system exhibits a remarkable variety of physical processes at all scales, pertaining to cooling and heating of the interstellar medium (e.g. Appleton et al 2017), star formation in shock regions (e.g. Guillard et al 2012), star cluster formation (e.g.…”
Section: Introductionmentioning
confidence: 99%